Zakat for Business Entity According to Fiqh and Positive Law in Indonesia (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2021)
This paper discusses zakat for business entity, which still require refinement of the concept if it is to be applied in Indonesia. Even though contemporary scholars have made it mandatory, an explanation is still needed regardingcriteria, calculation of nisab, awl, levels, procedures, including sanctions. This article uses qualitative data obtained through relevant literature sources. This article shows that there are differences in the views of scholars in viewing the obligatory zakat in this business association. Hanafiyah scholars are of the opinion that zakat on business entities assets is issued not in the name of the business entity, but on behalf of the owner of the property in the union, so that there may be business entity members who are subject to obligations and some are not because they do not meet the individual hawl and nisab standards. In the opinion of the syafi'iyah scholars, the benchmark is the business union, so that when the collective assets have reached the nisab, the zakat must be issued, even though if it is separated based on the rights of each individual there are still those who have not reached the minimum obligatory zakat.